Integrative RNA, miRNA, and 16S rRNA sequencing reveals immune-related regulation network for glycinin-induced enteritis in hybrid yellow catfish, Pelteobagrus fulvidraco ♀ × Pelteobagrus vachelli ♂ - Linyuan Yi; Aijie Mo; Huijun Yang; Yifan Yang; Qian Xu; Yongchao Yuan; Yongchao Yuan; Yongchao Yuan (Frontiers in Immunology)
Glycinin-induced foodborne enteritis is a significant obstacle that hinders the healthy development of the aquatic industry. Glycinin causes growth retardation and intestinal damage in hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × Pelteobagrus vachelli ♂), but its immune mechanisms are largely unknown. In the current study, five experimental diets containing 0% (CK), 1.74% (G2), 3.57% (G4), 5.45% (G6), and 7.27% (G8) immunological activity of glycinin were fed to juvenile hybrid yellow catfish to reveal the mechanism of the intestinal immune response to glycinin through RNA and microRNA (miRNA) sequencing and to explore the interrelation between immune molecules and intestinal microbiota. The results demonstrated that glycinin content in the posterior intestine increased significantly and linearly with the rise of dietary glycinin levels. More than 5.45% of dietary glycinin significantly reduced the nutritional digestion and absorption function of the posterior intestine. Notably, an obvious alteration in the expression levels of inflammatory genes (tnf-α, il-1β, il-15, and tgf-β1) of the posterior intestine was observed when dietary glycinin exceeded 3.57%. Sequencing results of RNA and miRNA deciphered 4,246 differentially expressed genes (DEGs) and 28 differentially expressed miRNAs (DEmiRNAs) between the CK and G6 groups. Furthermore, enrichment analysis of DEGs and DEmiRNA target genes exhibited significant responses of the MAPK, NF-κB, and WNT pathways following experimental fish exposure to 5.45% dietary glycinin. Additionally, at the level of 3.57% in the diet, glycinin obviously inhibited the increase of microbiota, especially potential probiotics such as Ruminococcus bromii, Bacteroides plebeius, Faecalibacterium prausnitzii, and Clostridium clostridioforme. In sum, 5.45% dietary glycinin through the MAPK/NF-κB/WNT pathway induces enteritis, and inflammatory conditions could disrupt micro-ecological equilibrium through miRNA secreted by the host in hybrid yellow catfish. This study constitutes a comprehensive transcriptional perspective of how intestinal immunity responds to excessive glycinin in fish intestines.